High-precision non-invasive RBC and HGB detection system based on spectral analysis - Wang, Yunyi; Li, Gang; Kong, Li; Lin, Ling (Analytical and bioanalytical chemistry, 2023)
Non-invasive blood composition analysis based on dynamic spectrum (DS) theory has gained significant attention due to its non-invasive, simple, and fast performance. However, most of the multi-wavelength photoplethysmography (PPG) detection devices used to obtain DS are composed of halogen light sources and spectrometers and cannot detect effective PPG signals in the visible light short band (400–620 nm), which limits the detection accuracy of blood components with significant absorption spectral differences in that band. Therefore, this paper designs a multi-wavelength spectral acquisition system that can measure high signal-to-noise ratio (SNR > 65 dB) PGG signals at wavelengths of 405, 430, 450, 505, 520, and 570 nm and combines this system with a halogen lamp spectrometer acquisition system for non-invasive blood component detection. Furthermore, this paper collects the DS of 272 subjects with the combined system and establishes a predictive model for DS with the content of red blood cell (RBC) and hemoglobin (HGB) components. The results show that, compared with the halogen lamp spectrometer acquisition system, the correlation coefficient (Rp) of RBC and HGB prediction model established by the combined system has increased by 0.0619 and 0.0489, respectively, and the root mean square error (RMSE) has decreased by 0.08 1e12/L and 0.85 g/L, which confirm the feasibility of the designed multi-wavelength spectrum acquisition system to enhance the accuracy of blood component detection.